Immunotherapy for cancer in people living with HIV: safety with an efficacy signal from the series in real life experience. (1st September 2019) - Spano, Jean-Philippe; Veyri, Marianne; Gobert, Aurélien; Guihot, Amélie; Perré, Philippe; Kerjouan, Mallorie; Brosseau, Solenn; Cloarec, Nicolas; Montaudié, Henri; Helissey, Carole; Flament, Thomas; Gounant, Valérie; et al.
Abstract : Objective: To report efficacy and tolerance of nivolumab or pembrolizumab, PD-1 inhibitors, in people living with HIV (PLWHIV) and cancer. Design: Series of PLWHIV cancer patients treated with anti-PD1 agents in real-life clinical practice. Methods: From May 2014 to January 2019, 575 HIV-infected patients have been discussed in the French CANCERVIH national multidisciplinary board and included in the network database. Twenty-three patients were treated with immune checkpoint inhibitors in daily practice. We report the demographic characteristics, CD4 + T-cell counts, HIV viral loads, safety and efficacy data of these 23 PLWHIV treated in routine practice with nivolumab or pembrolizumab for nonsmall cell lung cancer ( n  = 21), melanoma ( n  = 1) and head and neck cancer ( n  = 1) retrospectively collected from the database CANCERVIH network. The median CD4 + T-cell count at treatment initiation was 370 cells/μl (IQR: 125–1485). HIV viral load was undetectable in all patients. Results: As of 29 April 2019, with a median follow-up of 10.8 months (2.0–27.7), the median number of injections was 6 (IQR: 4–18). Only two grade 3 adverse reactions were reported (no toxic deaths or immune-related deaths). Among the 23 patients, a partial response was observed in five patients (22%), a stabilization for five (22%) and a progression in 13 (57%). Only one patient experienced a positive HIV viral load, but this occurred following ART interruption. Conclusion: Treatment with PD-1 inhibitors seems to have an efficacy signal and be well tolerated in PLWHIV, including impact on CD4 + lymphocyte count and HIV load, that should be monitored during treatment course (regarding real-life experience).